A brief history of the Freemasons the true story of the world's most powerful secret society - Ridley, Jasper (Robinson, 2008)
The history of the Freemasons has been often shrouded in mystery and suspicion. Since 1717, with the establishment of the Grand Lodge in London, the Freemasons have been a power within the nation, withstanding attacks from the Catholic Church, Hitler and public disapproval. Throughout the last three hundred years, the Freemasons have been influential in some of the most important turning points in History. Jasper Ridley explores the role of the society in both the American and French Revolutions and whether Mozart's "The Magic Flute" was an expose of secret rituals. He reveals that Pushkin, Winston Churchill, Booker T. Washington, Clark Gable, Walter Scott, members of the royal family and at least 16 US Presidents were all members.